The Molecular Effects of SGLT2i Empagliflozin on the Autophagy Pathway in Diabetes Mellitus Type 2 and Its Complications - Ranin Saad; Hagar Tadmor; Offir Ertracht; Nakhoul Nakhoul; Farid Nakhoul; Farber Evgeny; Shaul Atar (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus (T2DM), especially hyperglycemia, is associated with increased glucose cell toxicity and oxidative stress that can lead to irreversible damage in the kidney such as diabetic nephropathy (DN). Autophagy plays a key role in the degradation of damaged intracellular proteins in order to maintain intracellular homeostasis and cell integrity. The disturbance of autophagy is involved in the pathogenesis of diabetic nephropathy. We aim to investigate the molecular effect of sodium-glucose transporter 2 inhibitor (SGLT2i) on the expression of ATG5 and its downstream collaborator LC3-II in diabetic nice model. Material and Methods. We used eight weeks old male mice: twenty C57BL/6 wild type (C57BL/6), twenty BTBR ob/ob (DM), and twenty BTBR ob/ob that were treated with empagliflozin (DM+EMPA), FDA approved SGLT2i. Lysate from murine renal cortex was analyzed by Western blot and immunohistochemistry. ATG5, LC3B, and fibronectin expression were analyzed in murine kidney tissues. All mice were sacrificed 13 weeks after the beginning of the experiment. Results. Histological and Western blot analyses reveal decrease ATG5, LC3-II, and fibronectin levels at renal specimens taken from DM mice. EMPA treatment reduced T2DM mice body weight and blood glucose and increased urine glucose. Further, it upregulated all of the abovementioned proteins. Conclusions. Hyperglycemia reduces LC3-II and ATG5 protein levels which contribute to deficiencies in the autophagy process, with development and progression of DN. SGLT2i significantly reduces progression of DN and onset of end-stage renal disease in T2DM patients, probably through its effect on autophagy.